„Rewolucja faszystowska” w interpretacji Władysława Jabłonowskiego - Kiwior-Filo, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The interpretation of Fascism with regard to the origins of this phenomenon undertaken by Władysław Jabłonowski 1865–1956 — prominent literary critic, journalist and political activist, one of the co-founders of National Democracy — which was presented in the collection of his reflections titled Amica Italia published in 1926, was in basic agreement with the opinions of many renowned historiographers of the period who saw the seeds of the Fascist movement in the 19th-century nationalism and in social dissatisfaction resulting from peace treaties after World War I the myth of crippled victory and from Italian politics of later years. For Władysław Jabłonowski, “Fascist revolution” was the most significant process happening in Italy during the interwar period. It succeeded thanks to power, force, ardor, belief and participation of the huge multitudes of Italian citizens. It became a symbol of social order, erected upon nationalist ideas appropriated and incorporated by the Fascist movement. According to Jabłonowski, Fascism efficiently resisted international socialism and communism, simultaneously offering an alternative to democracy. New movement overcame stagnation of parliamentarianism, proposing efficient rule personified by Benito Mussolini whom Jabłonowski perceived as the leader of the revolution and statesman of great standing. “Fascist revolution,” being a combination of various factors, like nationalist ideology as a leading concept, national myth created by Fascism, active support of the masses, and “undeniable leadership” of Mussolini, saved Italy — in Jabłonowski’s opinion — from anarchy. Not hiding his pro-Fascist attitude, Jabłonowski was convinced that Fascism as a movement of “youthful and energetic elements that await action and enjoy struggle” will not desist its revolution until all of its opponents are forced to capitulate completely.
Keywords: faszyzm włoski; Mussolini, Benito (1883-1945); nacjonalizm; Włochy